2017
DOI: 10.18632/oncotarget.21401
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of inflammation-based scores in advanced hepatocellular carcinoma patients prior to treatment with sorafenib

Abstract: Background and AimsThe multikinase inhibitor sorafenib is the only currently approved drug for the indication of advanced hepatocellular carcinoma (HCC). It provides a limited gain in survival time but is frequently associated with adverse events. We currently lack simple prognostic factors in sorafenib-treated HCC patients. Various inflammation-based scores (IBSs) have been evaluated as predictors of tumor recurrence and survival in various malignancies (including HCC). The objective of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
2
25
1
1
Order By: Relevance
“…As is listed in Table 1 , all articles were published between 2014 and 2017 in English peer-reviewed journals. Among these articles, 16 articles 7 - 12 , 14 , 17 , 20 - 25 , 27 , 28 were from China, 4 articles 13 , 15 , 16 , 19 were from Italy, one was from Korea 18 and another was from France 26 . These articles included a variety of cancers, among them 6 for Hepatocellular carcinoma, 3 for Esophageal squamous cell carcinoma (ESCC), 3 for Gastric Cancer, 3 for colorectal cancer, one for Small Cell Lung Cancer (SCLC), one for Prostate cancer, one for Renal cell cancer, one for Biliary tract cancer, one for Malignant obstructive jaundice, one for non-small cell lung cancer (NSCLC) and one for Acral Melanoma.. As shown in Table 1 , the reference of 7 and 8 were performed in two independent patient populations, they separately had two HRs.…”
Section: Resultsmentioning
confidence: 99%
“…As is listed in Table 1 , all articles were published between 2014 and 2017 in English peer-reviewed journals. Among these articles, 16 articles 7 - 12 , 14 , 17 , 20 - 25 , 27 , 28 were from China, 4 articles 13 , 15 , 16 , 19 were from Italy, one was from Korea 18 and another was from France 26 . These articles included a variety of cancers, among them 6 for Hepatocellular carcinoma, 3 for Esophageal squamous cell carcinoma (ESCC), 3 for Gastric Cancer, 3 for colorectal cancer, one for Small Cell Lung Cancer (SCLC), one for Prostate cancer, one for Renal cell cancer, one for Biliary tract cancer, one for Malignant obstructive jaundice, one for non-small cell lung cancer (NSCLC) and one for Acral Melanoma.. As shown in Table 1 , the reference of 7 and 8 were performed in two independent patient populations, they separately had two HRs.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were conducted in Asia, mainly in China and Japan, 8 studies were conducted in America and Europe, and two were multicentered covering locations in western and eastern countries (17,21). Thirteen studies focused on the NLR as prognostic factors, one study analyzed the association between neutrophil count and survival outcome (25), three studies explored the PLR prediction function, one study investigated the prognostic function of the monocyte -to-lymphocyte ratio (MLR) (28) and one the lymphocyte-to-monocyte ratio (LMR) (33), and three studies reported on inflammation biomarkers as risk factors for survival, such as IL-17A, IL8, IL10, Ang-2, G-CSF, HGF, and leptin, etc.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…The detailed selection procedure was presented in Figure . Finally, a total of 26 articles (Absenger et al, ; Chen et al, ; Colloca, Venturino, & Guarneri, ; Conroy et al, ; Cox et al, ; Deng et al, ; Dirican et al, ; Du & Lu, ; Gao et al, ; Grenader et al, ; Grenader et al, ; Hala & Ahmed, ; Inoue et al, ; Jin et al, ; B. S. Lee et al, ; Liu et al, ; Lu et al, ; Neal et al, ; Park et al, ; Song et al, ; Suzuki et al, ; Szkandera et al, ; Wood et al, ; Ying et al, ; Zhou et al, , ) with 13,945 GI tumor patients were enrolled, and these cases were diagnosed with eight different kinds of digestive cancers, including three GI tract tumors, and five malignant neoplasms of the hepatobiliary pancreatic system. All these 26 research were evaluated in 9 different countries, including China (11 studies), UK (5 studies), Austria (2 studies), Japan (2 studies), South Korea (2 studies), Italy (1 study), France (1 study), Egypt (1 study), and Turkey (1 study).…”
Section: Resultsmentioning
confidence: 99%